Attention to food cues following media multitasking is associated with cross-sectional BMI among adolescents - Brand, John; Carlson, Delaina; Ballarino, Grace; Lansigan, Reina Kato; Emond, Jennifer; Gilbert-Diamond, Diane (Frontiers in Psychology, 2022)
Purpose: To measure attention to food cues following a multitask or a sustained attention single task, and further, to examine the associations with current weight status and excess consumption. Methods: Ninety-six 13- to 17-year-olds were fed a standardized meal and then had their attention to task-irrelevant food cues measured following completion of a single sustained attention task, media multitask, or a passive viewing control task. Participants then completed an eating in the absence of hunger paradigm to measure their excess consumption. Adolescents completed each condition on separate visits in randomized order. Attention to food cues was measured by computing eye tracking measures of attention, first fixation duration and cumulative fixation duration to irrelevant distractor images while participants played the video game, Tetris. Participants also had their height and weight measured. Results: Although not statistically significant, attention to task-irrelevant food cues was greatest following a media multitask and weakest following a task that engaged sustained attention when compared to a control. First fixation duration was positively and statistically-significantly associated with BMI-Z when measured following a multitask. Cumulative fixation duration was similar associated with BMI-Z, though the association was marginally statistically significant. There were also no associations between BMI-z and attention after the attention task or control task, nor any associations with attention to food cues and EAH. Conclusions: Among adolescents, we found that current adiposity was related to attention to task-irrelevant food cues following a multitask. Multitasking may perturb the cognitive system to increase attention to task-irrelevant food cues.